Ответ:
1)
[tex]x^{2} -4 = (x-2)(x+2)[/tex]
2)
[tex]25a^{2} - 36 = (5a+6)(5a-6)[/tex]
3)
[tex]x^{2} -2x + 1 = (x-1)^{2}[/tex]
4)
[tex]x^{3} + 27 = (x+3)(x^{2} -3x+9)[/tex]
5)
[tex]x^{2} +4x = x(x+4)[/tex]
6)
[tex]2x^{2} + x + 4x + 2 = x(2x+1) + 2(2x+1) = (2x+1)(x+2)[/tex]
Объяснение:
надеюсь правильно .......
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
1)
[tex]x^{2} -4 = (x-2)(x+2)[/tex]
2)
[tex]25a^{2} - 36 = (5a+6)(5a-6)[/tex]
3)
[tex]x^{2} -2x + 1 = (x-1)^{2}[/tex]
4)
[tex]x^{3} + 27 = (x+3)(x^{2} -3x+9)[/tex]
5)
[tex]x^{2} +4x = x(x+4)[/tex]
6)
[tex]2x^{2} + x + 4x + 2 = x(2x+1) + 2(2x+1) = (2x+1)(x+2)[/tex]
Объяснение:
надеюсь правильно .......